European Respiratory Society clinical practice guidelines: methodological guidance. Issue 1 (24th January 2022) - Nagavci, Blin; Tonia, Thomy; Roche, Nicolas; Genton, Celine; Vaccaro, Valerie; Humbert, Marc; Brightling, Christopher; Robalo Cordeiro, Carlos; Bush, Andrew
As one of the leading respiratory organisations, the European Respiratory Society (ERS) brings together physicians, healthcare professionals, scientists and other experts working in respiratory medicine. One of their roles is to provide guidance on clinical practice by developing high-quality clinical practice guidelines (CPGs). This is achieved by establishing specific task forces through an annual call for applications (except for short documents, for which applications can be submitted at any time [1]), and a rigorous selection and peer review process. Once approved, task force members, supported by ERS methodologists, work together for 2 years to develop CPGs using rigorous methodology, which, on satisfactory completion, are then adopted by ERS as official documents. ERS has published official methodological guidance for clinical practice guidelines. ERS recommends this to ensure that state-of-the-art guidelines are developed. https://bit.ly/3xP5SSr